Quantifying ADHD Symptoms in Open-Ended Everyday Life Contexts With a New Virtual Reality Task. Issue 11 (September 2022) - Seesjärvi, Erik; Puhakka, Jasmin; Aronen, Eeva T.; Lipsanen, Jari; Mannerkoski, Minna; Hering, Alexandra; Zuber, Sascha; Kliegel, Matthias; Laine, Matti; Salmi, Juha
Objective: To quantify goal-directed behavior and ADHD symptoms in naturalistic conditions, we developed a virtual reality task, EPELI (Executive Performance in Everyday LIving), and tested its predictive, discriminant and concurrent validity. Method: We collected EPELI data, conventional neuropsychological task data, and parent-ratings of executive problems and symptoms in 38 ADHD children and 38 typically developing controls. Results: EPELI showed predictive validity as the ADHD group exhibited higher percentage of irrelevant actions reflecting lower attentional-executive efficacy and more controller movements and total game actions, both indicative of hyperactivity-impulsivity. Further, the five combined EPELI measures showed excellent discriminant validity (area under curve 88 %), while the correlations of the EPELI efficacy measure with parent-rated executive problems ( r = .57) and ADHD symptoms ( r = .55) pointed to its concurrent validity. Conclusion: We provide a proof-of-concept validation for a new virtual reality tool for ecologically valid assessment of ADHD symptoms.